GOVERNMENT POLICY AND GLOBAL MARKET ENCOURAGE THE ACCELERATION OF HALAL CERTIFICATION PROGRAMS - Syarofi, Muhammad; Dasuki, Mohammad; Hamdi, Muhammad; Mu’awanah, Ulyatul (International Conference on Humanity Education and Society (ICHES), 2024)
Halal certificates are the main requirement for products to be accepted by the global market, so that every product gets legal legality in the form of a halal label, this obligation is still progressing slowly, because UUJPH has not been fully realized for halal product managers in Banyuwangi district, due to the low number of halal product producers who have halal certificates. , it is assumed that without a halal label the product will still be accepted and processing halal certification is difficult and complicated. This research aims to analyze government policies and the global market as drivers for accelerating the Banyuwangi MSME halal certification program. This research uses a qualitative approach, case study research type, the research subject is halal product MSMEs, Halal Product Process Companion, Banyuwangi Ministry of Religion's halal task force. Data collection by observation, interviews and documentation. Data analysis using the Miles and Huberman Interactive model and data validity using triangulation. The research results show that government policy Law no. 33 of 2014 concerning Halal Product Guarantees, provides the public with legal certainty, increases confidence in the consumption of halal products and provides understanding in the process of applying for halal certification, so that it can be used to strengthen the acceleration of the halal certification program. Apart from that, products that have halal certification can be used as a strategy to expand market share to reach the global market, and increase the sales turnover of halal product producers, and can be used as a strategy to strengthen the acceleration of the halal certification program.